Developing and validating a common body of knowledge for information privacy. (11th November 2019) - Lavranou, Rena; Tsohou, Aggeliki
Abstract : Purpose: This paper aims to present a common body of knowledge (CBK) for the field of information privacy, titled InfoPrivacy CBK. The purpose of the proposed CBK is to guide internet users to better understand the concept of information privacy and associate information privacy-related concepts. The InfoPrivacy CBK was created with an educational orientation to provide the basis for designing privacy awareness and training programs and organizing relevant educational material. Design/methodology/approach: The proposed CBK for information privacy was developed conceptually and includes five domains and four levels of analysis. It is illustrated with conceptual maps. The authors identified a variety of concepts related to information privacy and created a set of categories to categorize the concepts. They used, as inclusion criteria, both theoretical and practical information privacy aspects, so that the developed CBK can address the challenges of modern technologies for preserving information privacy. Findings: To validate and refine the conceptually developed CBK, the authors conducted an empirical research, in which seven information privacy experts participated. The experts commented largely positively for the structure and content of InfoPrivacy CBK, as well as for the extent to which it achieves the intended educational goals. Research limitations/implications: The proposed InfoPrivacy CBK was validated by a limited number of information privacy experts, mainly due to the lengthy and in-depth participation that was required. Practical implications: The InfoPrivacy CBK can be used primarily by privacy awareness and training programs developers, such as organizations, data protection officers, the state, educational policy makers and teachers. Social implications: Internet users will benefit from InfoPrivacy CBK by acquiring knowledge and skills from theoretically grounded training programs, which can enhance their awareness and critical thinking on issues related to the protection of their information privacy. This will lead to more privacy-aware online societies, communities, networks, etc. Originality/value: This work intends to bridge the existing gap in the literature through the creation of a novel CBK for information privacy; information privacy is a field for which no such research effort has been recorded. This paper offers important knowledge in the field of information privacy, which could be useful to both technological education designers and learners (students, employees, etc.).